2017
DOI: 10.1186/s13633-016-0041-7
|View full text |Cite
|
Sign up to set email alerts
|

Short stature and hypoparathyroidism in a child with Kenny-Caffey syndrome type 2 due to a novel mutation in FAM111A gene

Abstract: BackgroundHypoparathyroidism in children is a heterogeneous group with diverse genetic etiologies. To aid clinicians in the investigation and management of children with hypoparathyroidism, we describe the phenotype of a 6-year-old child with hypoparathyroidism and short stature diagnosed with Kenny-Caffey syndrome (KCS) Type 2 and the subsequent response to growth hormone (GH) treatment.Case presentationThe proband presented in the neonatal period with hypocalcemic seizures secondary to hypoparathyroidism. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 26 publications
4
30
1
1
Order By: Relevance
“…These results raised the possibility that FAM111A might have autocleavage activity in vivo. Interestingly, germline mutations have been found in FAM111A in patients with Kenny-Caffey syndrome (KCS) and osteocraniostenosis (OCS) [38][39][40][41] , and it has been postulated that these mutations may cause gain-of-function FAM111A activity because the mutations are always heterozygous and no loss-of-function mutations (i.e., deletions and truncations) have been reported 38 . We therefore tested whether the mutations found in KCS and OCS patients produce constitutively active FAM111A.…”
Section: Resultsmentioning
confidence: 99%
“…These results raised the possibility that FAM111A might have autocleavage activity in vivo. Interestingly, germline mutations have been found in FAM111A in patients with Kenny-Caffey syndrome (KCS) and osteocraniostenosis (OCS) [38][39][40][41] , and it has been postulated that these mutations may cause gain-of-function FAM111A activity because the mutations are always heterozygous and no loss-of-function mutations (i.e., deletions and truncations) have been reported 38 . We therefore tested whether the mutations found in KCS and OCS patients produce constitutively active FAM111A.…”
Section: Resultsmentioning
confidence: 99%
“…3,7 In silico analyses also showed that this de novo variant would not significantly affect protein function. 7,14 We performed a three-dimensional protein model to obtain an insight on the consequences of the altered amino acid within protein structure. As shown in ►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…9 Growth hormone (GH) treatment seems to play a limited role in the management of these patients, even with KCS2. 8,9,14,16 However, a study performed an evaluation of the use of GH in five patients with KCS and four of them showed a normal response. 17 Moreover, another study reported a patient who underwent treatment with GH therapy (0.5 IU/kg/wk) at 7 years and 5 months of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological examination showed prominent forehead, narrow nasal base with pinched nasal tip, apparent small eyes, and broad cheeks (Table S1), leading to treatment discontinuation for 8 months, until a new hypoparathyroidism episode (Table S1) (p.Arg569His) in FAM111A gene. This variant was classified as pathogenic based on its previous description in patients with KCS2 (Abraham et al, 2017;Guo et al, 2014;Isojima et al, 2014;Nikkel et al, 2014;Unger et al, 2013), and the absence in 60,000 control individuals on Exome Aggregation Consortium (ExAC).…”
Section: Case Reportmentioning
confidence: 99%